PENGEMBANGAN PROGRAM EDUKASI SEKSUAL SEHAT BERBASIS CSE PADA REMAJA SEKOLAH MELALUI PENDEKATAN PARTICIPATORY ACTION RESEARCH - Shinta Oktavia; Mardian Syahputra, Najwa Khoirunnisa, Zahratul Melcha, Muhammad Yusuf, Ridho Zakhwan Aqfazaro, Tri A (Adiba Aisha Amira, 2026)
Adolescence is a developmental stage characterized by vulnerability to issues related to relationships, sexuality, and reproductive health, particularly when sexual literacy is limited. This study aimed to develop and implement a healthy sexuality education program based on Comprehensive Sexuality Education (CSE) using a Participatory Action Research (PAR) approach. The study involved 33 senior high school students aged 15–18 years who were actively engaged in the processes of problem identification, planning, implementation, and program evaluation. The intervention was delivered through an interactive learning medium, the Card of Sex Education (CASED), using reflective group discussions. Program effectiveness was evaluated using a pre-test and post-test design developed in accordance with UNESCO guidelines. The results indicated a significant increase in participants’ knowledge after the intervention (Z = −3.662; p < 0.001) with a strong effect size. These findings suggest that CSE-based sexuality education combined with a participatory approach is effective in enhancing adolescents’ sexual literacy and life skills.